2014
DOI: 10.1177/1352458514556295
|View full text |Cite
|
Sign up to set email alerts
|

Non-Gaussian diffusion MRI of gray matter is associated with cognitive impairment in multiple sclerosis

Abstract: Background Non-Gaussian diffusion imaging by using diffusional kurtosis imaging (DKI) allows assessment of isotropic tissue as of gray matter (GM), an important limitation of diffusion tensor imaging (DTI). Objective In this study, we describe DKI and DTI metrics of GM in MS patients and their association with cognitive deficits. Methods Thirty-four patients with relapsing-remitting MS and 17 controls underwent MRI on a 3T scanner including a sequence for DKI with 30 diffusion directions and 3b values for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
47
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 35 publications
5
47
2
Order By: Relevance
“…As such, a decrease of MK is believed to be linked to a loss of microstructure. Furthermore, in line with our findings, a decrease of MK has been observed in the grey matter of the spinal cord of MS patients (Raz et al , 2013) and a very recent study by Bester et al who reported a decrease of MK in cortical grey matter of MS patients, which also correlated with cognitive deficits (Bester et al , 2014). …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…As such, a decrease of MK is believed to be linked to a loss of microstructure. Furthermore, in line with our findings, a decrease of MK has been observed in the grey matter of the spinal cord of MS patients (Raz et al , 2013) and a very recent study by Bester et al who reported a decrease of MK in cortical grey matter of MS patients, which also correlated with cognitive deficits (Bester et al , 2014). …”
Section: Discussionsupporting
confidence: 93%
“…Hence DK metrics estimate the degree of diffusion restriction, which is related to tissue complexity in both white and grey matter (Hui et al, 2008; Jensen and Helpern, 2010; Jensen et al , 2005; Wu and Cheung, 2010). Sensitivity of DKI to detect microstructural alterations has been demonstrated in normal developing (Paydar et al , 2014) and aging humans (Coutu et al , 2014; Falangola et al , 2008) and patients suffering from several neurological disorders including MS and other demyelinating diseases (Bester et al , 2014; Kimura et al , 2014; Raz et al , 2013; Yoshida et al , 2013). …”
Section: Introductionmentioning
confidence: 99%
“…6,90,[104][105][106][107] Cross-sectional studies suggest that brain volume loss may be a better predictor of cognitive impairment than focal white matter lesion burden. 50,108 A recent investigation in patients with RIS reported cognitive impairment in 28% of patients and an association of higher T1 lesion volumes and lower cortical volumes with worse cognitive performance.…”
Section: Diffuse Gray Matter Damagementioning
confidence: 99%
“…The successful management of MS and monitoring of treatment response thus call for new markers with an increased sensitivity and specificity for the disease’s various pathological processes. Unlike conventional MRI, diffusion MRI techniques, including diffusion tensor imaging (DTI) and diffusional kurtosis imaging (DKI) [7], are sensitive to diffuse microscopic injury in the normal-appearing white matter (NAWM) and gray matter of MS patients [810]. Both DTI and DKI metrics, however, are empirical diffusion measures and lack microstructural and pathological specificity [7].…”
Section: Introductionmentioning
confidence: 99%